Peculiarities of children’s health status after acute respiratory viral infections: a look at the problem, ways to solve it - Yu.V. Marushko; T.V. Marushko; O.A. Dmytryshyn; O.A. Bovkun; T.V. Iovitsa; B.Ya. Dmytryshyn (Zdorovʹe Rebenka)
Background. The article reviews literature data on the peculiarities of changes in the health status of children after acute respiratory viral infections (ARVI) of various etiologies and the development of post-viral asthenic syndrome accompanied by physical, cognitive, emotional, and psychological symptoms that significantly impair the quality of life. The purpose of the study is to summarize the literature data on the features, mechanisms of development of changes in the health status of children after ARVI, and methods to correct these disorders, in particular by prescribing herbal remedies. Materials and methods. Bibliographic and information-analytical research methods were used. A theoretical analysis of scientific data from the search databases PubMed, Web of Science, Scopus, Google Scholar, and British Medical Journal for the last 10 years was carried out on the possibility of using, efficacy, safety, and properties of oregano, thyme, rose, small-leaved linden, hibiscus sabdariffa, calendula officinalis, black currant. Results. According to the literature review, the incidence of post-viral asthenic syndrome in children is 36.8 %, with cognitive-emotional changes (84 %), sleep disturbances (74 %), decreased appetite (64 %), and headaches (52 %) dominating in the clinical picture. The persistence of these manifestations hinders the adequate restoration of the child’s adaptive capacity and the fight against hypoxia, acidosis, metabolic disorders due to ARVI, and post-viral asthenic syndrome. This determines the urgency of finding appropriate methods of correction with etiopathogenetic (inhibition of oxidative stress, reduction of acidosis and hypoxia, restoration of liver function), immunoregulatory (improvement of the immune system), and symptomatic (improvement of appetite) effects. The analysis of scientific data on the properties of oregano, thyme, rose, small-leaved linden, hibiscus sabdariffa, calendula officinalis, black currant made it possible to verify the possibility of using this combination to correct the clinical manifestations of post-viral asthenic syndrome in children and restore their health after ARVI. Conclusions. Phytocombination of oregano, thyme, rose, small-leaved linden, hibiscus sabdariffa, calendula officinalis, black currant can be recommended for the restoration of children’s health after ARVI, influenza, COVID-19, adenovirus infection, and children with clinical manifestations of post-viral asthenic syndrome due to the properties that provide antioxidant, anti-inflammatory, antiviral effects, a positive impact on the gastrointestinal tract, nervous and immune systems.